ANALISIS PENGAKUAN PENDAPATAN TERHADAP LABA RUGI PADA PERUSAHAAN PT. INDOTERAS SUMATERA MEDAN - REBECCA EVADINE (JURNAL ILMIAH MAKSITEK, 2019)
Revenue recognition is the process of recording the cash flow coming in on the transfer of goods, rendering of services, or other activities. Revenue can be recognized when the transaction occurs or after the transaction is completed. Generally, revenue recognition and accrual basis can be critical event basis. In recognition of the critical event revenue basis, revenues are recorded directly as sales activities or the provision of services and profit is calculated based on the income received at the time. The recognition of revenue related to the company's income. This is due if the recognition of revenue that do not will result in the financial performance information is presented in the form of income that the company be inaccurate, because the revenue recognized would affect the company's income. The purpose of this study was to determine whether the recognition of revenue on the income the company of PT. Indoteras Sumatra, Medan in accordance with Statement of Financial Accounting Standards No. 23 About Revenue. The data used in this research is secondary data. The data collection techniques used by the author in this study is observation, interview and documentation. To analyze the data obtained by the authors using Descriptive Analysis Method. The results of this study indicate that that the recognition of revenue applied by PT Indoteras Sumatra, Medan in accordance with Statement of Financial Accounting Standard 23 on revenue. But still in need of correction on the recognition of rental income and Warehouse Building.